Views of MBBS Students and Healthcare Workers on Quality Improvement in Tertiary Care Hospitals - Patel, Adityaraj; Dalavi, Rupesh Dinakar; Hussain, Aqsa; Umesh KP, Namita; Upadhyay, Jyoti Kumari; Goyal, Chiksha; Runthla, Hemang; Divyansh, Divyansh; Garg, Hemant Kumar; Singh, Brijmohan (Journal of Neonatal Surgery, 2025)
Quality improvement (QI) in healthcare is pivotal for enhancing patient outcomes, safety, and system efficiency. This cross-sectional study explores the perceptions of QI among 100 MBBS students and interns from NIMS University, Jaipur, Rajasthan, and 60 nursing staff from Government Medical College, Greater Noida, Uttar Pradesh. Using a validated Likert-scale questionnaire, we assessed awareness, attitudes, and engagement with QI initiatives. Findings revealed moderate to high awareness among medical students, with interns demonstrating greater familiarity with QI tools such as Plan-Do-Study-Act (PDSA) cycles. Nursing staff exhibited practical engagement but limited formal training in QI methodologies. Barriers included lack of structured training, hierarchical constraints, and limited interprofessional collaboration. The study underscores the need for integrated QI education across disciplines and recommends institutional support for capacity building. These insights can inform curriculum reforms and policy-level interventions to foster a culture of continuous improvement in tertiary care settings.